Endometrial Regenerative Cell-Derived Exosomes Attenuate Experimental Colitis through Downregulation of Intestine Ferroptosis. (22nd August 2022) - Zhu, Yanglin; Qin, Hong; Sun, Chenglu; Shao, Bo; Li, Guangming; Qin, Yafei; Kong, Dejun; Ren, Shaohua; Wang, Hongda; Wang, Zhaobo; Zhang, Jingyi; Wang, Hao
Abstract : Background . Endometrial regenerative cells (ERCs) have been identified to ameliorate colitis in mice; however, whether exosomes derived from ERCs (ERC-exos) own similar effects on colitis remains unclear. Ferroptosis, an iron-dependent cell programmed death form, has been reported to promote inflammation in UC. Thus, in this study, whether ERC-exos can treat colitis and regulate intestine ferroptosis will be explored. Methods . In this study, iron, malondialdehyde (MDA) production, glutathione (GSH) synthesis, and acyl-CoA synthetase long-chain family member (ACSL) 4 and glutathione peroxidase 4 (GPX4) expressions were measured in colon samples from healthy people and UC patients to explore the effects of ferroptosis. In vitro, ERC-exos were cocultured with ferroptosis inducer erastin-treated NCM460 human intestinal epithelial cell line, and ferroptotic parameters were measured. In vivo, colitis was induced by 3% dextran sulfate sodium (DSS) in BALB/c mice, and animals were randomly assigned to normal, untreated, and ERC-exos-treated groups. The Disease Activity Index (DAI) score, histological features, tissue iron, MDA, GSH, ACSL4, and GPX4 were measured to verify the role of ERC-exos in attenuating UC. Results . Compared with healthy people, UC samples exhibited higher levels of iron, MDA, and ACSL4, while less levels of GSH and GPX4. In vitro, the CCK-8 assay showed that ERC-exos rescued erastin-induced cell death, and ERC-exos treatment significantly increased the levels of GSH and expression of GPX4, while markedly decreasing the levels of iron, MDA, and expression of ACSL4. In vivo, ERC-exos treatment effectively reduced DAI score, ameliorated colon pathological damage, and improved disease symptoms. Moreover, ERC-exos treatment further enhanced the levels of GSH and the expression of GPX4 but reduced the levels of iron, MDA, and expression of ACSL4 in the colon of colitis mice. Conclusions . Ferroptosis was involved in the pathogenesis of UC, and ERC-exos attenuated DSS-induced colitis through downregulating intestine ferroptosis. This study may provide a novel insight into treating UC in the future.